(untitled) (African Journal of Biomedical Research, 2021)
Maternal mortality is an important health indicator of any country. The use of partograph would engender a remarkable reduction in the number because abnormality in labor would be identified early for prompt intervention. A cross sectional descriptive survey design was used to assess knowledge and utilization of partograph in monitoring of labor by nurses and midwives in a tertiary health institution in South- South, Nigeria. Three research questions and one hypothesis was formulated for the study. Eighty six midwives working in maternity annex were used. The instrument for data collection was a self developed structured questionnaire and checklist. The checklist was used to extract information needed to fill the partograph. Data was analyzed using simple percentages and hypothesis was tested using chi square test analysis. Results revealed that 73 (84.9%) midwives had good knowledge of partograph. In utilization of partograph in labor monitoring, 84 partographs were properly filled. The x2 analysis revealed a statistical relationship between level of knowledge, years of experience and utilization of partograph when the calculated chi square of 28.93 and 30.82 were both greater than the critical X2 of 3.841 and 7.815 with 1 and 3 degrees of freedom respectively. Factors hindering utilization were lack of knowledge, non-availability, time consuming, shortage of staff and detailed to complete. Based on these, training of nurses and midwives on the use of the partograph with periodic workshops and seminars and a mandatory hospital policy were recommended as this will helped in monitoring of maternal and fetal wellbeing. KEY WORDS: Partograph, Knowledge, Utilization, Nurses, Midwives, Labour, Tertiary Institution